Flipping the classroom to enhance student engagement in first-year statistics education - Da Silva, Liza (University of the Free State, 2023)
This study explores the effectiveness of a flipped classroom (FC) variant based on students engaging with content outside of class by viewing video-lectures. The flipped classroom encouraged students to take responsibility for their own learning. When they were unclear on specific concepts, they could use technology to collaborate with their peers or the lecturer. To encourage viewing of the videos, an incentive was given in the form of weekly assessments that the students had to complete, which formed part of their semester mark. A randomised pre-test-post-test control design was implemented in a sample of Extended Curriculum Programme (ECP) students in a first-year statistics course. The FC approach was exercised in the experimental group (Group A), while the control group (Group B) received traditional face-to-face lecturing. A comparison between the final scores of Group A and Group B was used to give insight into the effectiveness of this treatment. Each group consisted of 67 students. The results showed that a video-based lecturing pedagogy significantly improved ECP students’ final scores. In this study, students applied different learning activities such as inquiring about information, watching video-lectures, and practically applying the knowledge studied when completing weekly online assessments. Students collaborated with the lecturer and their peers via e-mail or WhatsApp to thoroughly understand the subject. Therefore, active learning, which fosters deep learning, was encouraged. This finding is consistent with the constructivist pedagogical theory, which emphasises the importance of interaction with others in knowledge construction and develops a deeper understanding of the subject matter. These findings align with other studies that report positive student perceptions of blended learning in first-year statistics. This research found that the FC intervention, as applied by the researcher, resulted in a significant increase in student performance on their final marks, which indicates that the FC approach is an important pedagogical approach to increase student achievement. Further, the results confirmed that the FC approach improved student engagement. One factor that significantly enhanced student engagement was the students’ preferred place of study. Students from the experimental group studying at their place of residence significantly outperformed students from the traditional group who studied at their place of residence. Another factor that indicated that student engagement was enhanced was that student-staff interaction significantly increased in the experimental group. Some interesting findings surfaced. An unexpected gender finding evidenced that male students in the experimental group significantly outperformed the male students in the control group. Furthermore, when the place of study was examined, the experimental group performed better when studying at their residences. Many participants in Group A showed a favourable perception towards the videoed-lecturing approach as they enjoyed watching video-lectures at their own pace. They also indicated that they prefer this new variant of flipping because it motivated them to learn. From the survey analysis, many students preferred watching video-lectures at their own pace, time, and space. An overwhelming portion of the participants indicated that the use of technology was pivotal in their learning. It was also derived that the more students participated in all their assessments, the higher their final score was.
Thesis (Ph.D(Higher Education Studies))--University of the Free State, 2023